2016
DOI: 10.3934/genet.2016.3.167
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene polymorphisms in Sudanese children with type 1 diabetes

Abstract: Type 1 diabetes mellitus (T1DM) is a T cell mediated autoimmune disease. Vitamin D was found to suppress the incidence of diabetes when bind to its receptor (VDR), probably by suppressing T cell activations. Thus the VDR gene polymorphism may have an impact on pathophysiology of this disease. Since there was no consistent association between VDR polymorphisms and the risk of T1DM, this study aimed to investigate a VDR gene polymorphism in Sudanese children with T1DM. We examined the VDR gene Bsm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This high variability and rapidly increased incidence of T1DM in various world populations could be owing to differences in ethnic background and nationality. These 4 VDR gene polymorphisms were examined for their connection with T1DM in a variety of populations, such as JApan, India, Kuwait, Iran, Turkish, and Finland, with mixed results (16,17). A South Indian analysis revealed that the b-allele of the VDR gene, BsmI polymorphism, was linked to T1DM (18).…”
Section: Resultsmentioning
confidence: 99%
“…This high variability and rapidly increased incidence of T1DM in various world populations could be owing to differences in ethnic background and nationality. These 4 VDR gene polymorphisms were examined for their connection with T1DM in a variety of populations, such as JApan, India, Kuwait, Iran, Turkish, and Finland, with mixed results (16,17). A South Indian analysis revealed that the b-allele of the VDR gene, BsmI polymorphism, was linked to T1DM (18).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, no significant association between three VDR gene polymorphisms ( Bsm I, Apa I and Taq I) and T1DM was detected in patients from Chile [27]. The data from Sudan, showed an association of two VDR gene polymorphisms ( Bsm I and Taq I) with T1DM [28]. In a study from Pakistan, VDR gene polymorphisms Fok I and Apa I were found to be associated with T1DM while no association was found with the Taq I polymorphism [29].…”
Section: Introductionmentioning
confidence: 99%
“…The primers of the VDR gene were designed based on previous literature. 19 The PCR condition used for Bsm I as followed: an initial denaturation of 3 min at 94 °C, followed by denaturation of 30 s at 62 °C, and extension of 1 min at 72 °C for 30 cycles, and a final extension of 5 min at 72 °C. The PCR condition used for amplification of Apa1 as follows; 94 °C for 10 min, and 30 cycles using the following temperature profile: 94 °C for 1 min, 62 °C for 1 min, 72 °C for 1 min, and final elongation for 5 min.…”
Section: Genotyping Of Vdr Gene Polymorphic Variantsmentioning
confidence: 99%